Evaluasi Pembelajaran Aktif dalam Meningkatkan Motivasi Belajar Kitab Kuning Santriwati di Dayah MUDI Mesjid Raya Samalanga - Juniati, Raudhatul (LaKaspia, 2024)
Active learning is recognized as an effective approach to enhancing student engagement and learning motivation, including in pesantren (Islamic boarding schools) where classical Islamic texts (kitab kuning) are the main focus of study. The background of this research stems from the limited studies addressing the effectiveness of active learning methods in the teaching of kitab kuning within traditional pesantren settings. This study aims to evaluate how far active learning can improve the learning motivation of female students (santriwati) at Dayah MUDI Mesjid Raya Samalanga. A qualitative descriptive method was employed through literature review, in-depth interviews with 2 heads of teaching departments, 3 kitab kuning teachers, and 5 class II students, as well as direct classroom observations. The findings indicate that active learning fosters a more interactive learning atmosphere, reduces learning fatigue, and enhances students’ confidence in understanding classical texts. The main conclusion of this research is that active learning is relevant and applicable as an innovative strategy while maintaining the traditional values of pesantren education. The contribution of this study lies in strengthening the adaptive teaching approach of kitab kuning to meet students’ needs and contemporary challenges.